Secular, religious or spiritual? A sociological portrait of UK mindfulness teachers - Arat, Alp; Hemming, Peter (2025)
Mindfulness is commonly defined in the public and professional realms as a secular therapeutic technique, but less attention has been paid to the practitioners at the vanguard of the contemporary UK mindfulness milieu and the extent to which their personal beliefs align with this profile. Drawing on a nationwide survey of 768 teachers of mindfulness, as well as 82 semi-structured interviews and a focus group with selected mindfulness practitioners, this article presents a detailed sociological portrait of UK mindfulness teachers, including their religious and spiritual identities, understandings of mindfulness, and strategies for negotiating these across personal and professional domains. The analysis reveals a far more spiritual cohort than might have been assumed, raising questions about the nature, function and significance of increasingly widespread mindfulness teaching practices in Western societies, and offering insights into the evolution of contemporary relations between ‘the secular’, ‘the religious’ and ‘the spiritual’ within the modern world.
Keywords: Wellbeing; Spirituality; Secular; Religion; Modernity; Mindfulness; Meditation; Health